Urgensi Pengaturan Hukum di Era Digitalisasi - Silalahi, Wilma; Djaja, Benny; Sudirman (Journal of Business, Management, and Social Studies, 2025)
The primary purpose of this research is to examine the integration of digital technology, specifically digital certification and signatures, into the notarial process in the current legal framework. The research employs a juridical-normative legal research methodology. This approach involves analyzing existing laws, regulations, and legal principles (the “normative” aspect) to address the legal problem at hand. The findings suggest that when consumers are faced with limited choices, such as accepting unfavorable terms or discontinuing service, informational and normative conformity significantly influence continuance intention. Factors such as perceived security, service quality, satisfaction, and perceived usefulness are found to moderate the relationship between conformity and continuance intention. Additionally, previous experience, trust, and self-efficacy emerge as strong determinants of users’ willingness to reuse or abandon the service after policy disruptions. The study found that while it is technologically possible to create and sign notarial deeds digitally, there are explicitly no laws or regulations that govern this process.